The positive relationship between the Alternative Healthy Diet Index and serum klotho levels: A cross-sectional analysis in middle-to-older Americans - Chaoshun Zheng; Longsheng Zhang; Yueyue Guo; Chuchun Lin; Xuhui He (PLoS ONE, 2025)
Background and aim The Alternative Healthy Eating Index (AHEI-2010) is a dietary index associated with chronic diseases and serves as an important metric for assessing the healthiness of one’s diet. Serum Soluble Klotho (S-Klotho) is a protein related to anti-aging. There is currently a lack of research on the relationship between AHEI and S-Klotho. This study evaluated the relationship between the AHEI index and S-Klotho in the U.S. middle-aged and elderly population from the National Health and Nutrition Examination Survey (NHANES) 2011–2016. Methodology This study includes 6,305 middle-aged and elderly participants (aged 40–79 years old). The interrelationship between the AHEI-2010 and S-klotho concentration was explored using multivariate regression models, and the nonlinear relationship between the two was investigated through curve fitting. The stability of this relationship in different populations was explored through subgroup analysis. Results There was a positive correlation between AHEI and S-klotho (β=1.1, 95% CI: 0.1, 2.1, P = 0.035). The multivariate-adjusted β and 95% confidence intervals (CIs) from the lowest to the highest AHEI-2010 categories (＜31.9, 31.9–39.3, 39.3–47.9, and > 47.9) were 0.0 (reference), 15.7 (-13.5, 44.9), 12.5 (-16.5, 41.6), and 31.9 (2.9, 60.9), respectively. The curve fitting found that the relationship between AHEI-2010 and S-Klotho is essentially linear, with S-Klotho levels increasing linearly as AHEI improves. Conclusion AHEI is positively associated with S-Klotho levels in American middle-to-older adults. Further research is needed to elucidate the causal relationship and specific mechanisms.